Reading Up Middle-Class Readers and the Culture of Success in the Early Twentieth-Century United States - Blair, Amy (Temple University Press, 2012)
A person who reads a book for self-improvement rather than aesthetic pleasure is "reading up." Reading Up is Amy Blair's engaging study of popular literary critics who promoted reading generally and specific books as vehicles for acquiring cultural competence and economic mobility. Combining methodologies from the history of the book and the history of reading, to mass-cultural studies, reader-response criticism, reception studies, and formalist literary analysis, Blair shows how such critics influenced the choices of striving readers and popularized some elite writers. Framed by an analysis of Hamilton Wright Mabie's role promoting the concept of "reading up" during his ten-year stint as the cultivator of literary taste for the highly popular Ladies' Home Journal, Reading Up reveals how readers flocked to literary works that they would be expected to dislike. Blair shows that while readers could be led to certain books by a trusted adviser, they frequently followed their own path in interpreting them in unexpected ways.